2020
DOI: 10.21203/rs.3.rs-38745/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual Function and Metabolic/Hormonal Changes in Women Using Long-Term Hormonal and Non-Hormonal Contraceptives: A pilot study.

Abstract: Background: Female sexual dysfunction is a common condition that negatively impacts the emotional health and quality of life of the affected individuals. Long-acting reversible contraceptives (LARCs) are becoming increasingly popular due to their effectiveness and convenience. LARCs can be hormonal (etonogestrel releasing implant—ENG and Levonorgestrel intrauterine system—LNG) or non-hormonal (copper intrauterine device—CuIUD and copper-silver intrauterine device—SIUD). There are very few studies that assess t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In literature, there were different studies examined the effect of contraceptives on sexuality. FSD was lower in women who used hormonal methods in our study, which was consistent with previous research (25,37), but contradictory to those of other research (3,12,28,47,48). In women who used hormonal methods, studies found that desire (14), arousal (12,14,18), orgasm (12), and total FSFI scores (14,47) were low, but vaginal dryness (12) and pain (18) were high According to these studies, contraceptive has a negative impact on sexuality by decreasing circulating testosterone levels as well as serum levels of estradiol and progesterone.…”
Section: Discussionsupporting
confidence: 81%
“…In literature, there were different studies examined the effect of contraceptives on sexuality. FSD was lower in women who used hormonal methods in our study, which was consistent with previous research (25,37), but contradictory to those of other research (3,12,28,47,48). In women who used hormonal methods, studies found that desire (14), arousal (12,14,18), orgasm (12), and total FSFI scores (14,47) were low, but vaginal dryness (12) and pain (18) were high According to these studies, contraceptive has a negative impact on sexuality by decreasing circulating testosterone levels as well as serum levels of estradiol and progesterone.…”
Section: Discussionsupporting
confidence: 81%
“…In a previous randomized trial, we found reduced sexual activity among participants randomized to injectable progestogens vs. the copper T 380 intrauterine device (IUD) ( 10 , 11 ). The etonogestrel implant and the DMPA-IM have been associated with impaired sexual function ascribed to suppressed estrogen and/or androgen levels ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%